Preserving Mojiang Hani hand weaving techniques: understanding complexity for culture and sustainable development - Mingquan, Liu; Yahaya, Siti Rohaya; Chunli, Guo; Yan, Huang (SHPMedia Sdn Bhd, 2024)
Mojiang, located in the southern region of Yunnan Province, China, serves as the historical abode of the industrious and intellectually rich Hani community, boasting a heritage spanning thousands of years. The traditional costumes of the Mojiang Hani people stand as integral bearers of their national culture, adorned with intricately handwoven elements. However, the advent of modern technology and shifts in the social environment have precipitated a marked decline in the prevalence of handwoven techniques within the decorative aspects of traditional costumes. This jeopardizes the continuity of a craft that is deeply woven into the fabric of their cultural identity. This research employs a methodical combination of observation and interviews to purposefully collect data on Mojiang Hani hand weaving techniques. The findings illuminate that the gradual disappearance of these techniques is intricately linked to their inherent complexity, manifesting across five dimensions: classification, materials, process, patterns, and forms. In response to these complexities, the research proposes judicious recommendations aimed at the effective preservation and transmission of Mojiang Hani hand weaving techniques and, by extension, their traditional culture. Beyond immediate preservation efforts, these suggestions form a solid foundation for future research endeavors and the sustainable development of Mojiang Hani hand weaving techniques, fostering a continuum of cultural heritage in the face of contemporary challenges